TOTAL ESCHERICHIA COLI IN BROILER FECES AT VARIOUS AGES IN BADUNG REGENCY - Krisis Mariani Buulolo; I Ketut Suada; I Putu Sampurna (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Broiler chickens are quality meat-producing chickens and are known to the public with various advantages, feces are a food process accompanied by urine and undigested food residues. The purpose of this study is to determine the total number of escherichia coliw bacteria in the feces of broiler chickens of various ages in Badung Regency. This study aims complete random design consisting of 3 location factors, namely Petang District, Abiansemal District, Mengwi District. The broiler chicken feces sample taken is 2-3 grams in each farm. In this study, the culture method of escheriachia coli bacteria uses the spread method on Methene Blue agar eosin media.The sample is characterized by metallic green colonies and black dots in the middle of the colony. The analysis of the data into the Y log before being analyzed to see the number of differences in the number of E. coli bacteria is carried out by variety analysis, if there is a real difference (P<0.05) then it is continued with the Duncan Multiple Distance test. The total research results of Escherichia coli bacteria are 8,973 in the evening of 1-21 days and 8,640 in the evening of 22-35 days and 8,640 in Mengwi District and 8,640 in 1-21 days and 8,640 in 22-35 days and 8,536 in Abiansemal District at the age of 1-21 days and 8,536 in 22-35 days. It can be concluded that the Total Escherichia coli Bacteria in broiler Chicken Feces in Petang District, Mengwi District, Abiansemal District has a very real effect (P<0.05). Further research is needed on humid environmental conditions with different types of cages in broiler chickens.